PENERAPAN DOUBLE TRACK SYSTEM TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN DAN PERBURUAN SATWA YANG DILINDUNGI - Fadhel Halilintar,; Slamet Tri Wahyudi, (Magister Kenotariatan Program Pascasarjana Universitas Islam Malang, 2022)
Hunts and wildlife trafficking that are protected are serious crimes because beyond threatening the environment the result of these crimes also causes harm to the state, it is not only because its economic factor In modern targeting systems, it is known as the double track system, which measures measures of criminal sanctions across two lines, and criminal penalties for assessing the convictions of convicted felons, which is already an international trend as a result of their inherent inaction. The purpose of this writing is to review how the ideal formulation for sanctions against the protected criminal hunts and animal trade. The kind of research in this study is normative research with a conceptual approach as well as a constitutional approach, In the study, it was found that with the absence of a minimum sentence against the convicted felons and wildlife trafficking protected in act no. 5 in 1990 resulted in a lightening of the sentence that was rendered so as not to have a lasting deterrent to those convicted of hunts and protected animal trafficking as ineffective.